How do you find the derivative of f(x) = arctan(cos(3x))f(x)=arctan(cos(3x))?

1 Answer
May 29, 2017

=-(3sin(3x) )/(1+cos^2(3x))=3sin(3x)1+cos2(3x)

Explanation:

d/dx(tan^-1(cos(3x)))ddx(tan1(cos(3x)))

Step 1. Use the chain rule
d/dx(tan^-1(cos(3x)))=(d(tan^-1(u)))/(du)(du)/(dx)ddx(tan1(cos(3x)))=d(tan1(u))dududx,

where u=cos(3x)u=cos(3x) and d/(du)(tan^-1(u))=1/(1+u^2)ddu(tan1(u))=11+u2

=(d/dx(cos(3x)))/(1+cos^2(3x))=ddx(cos(3x))1+cos2(3x)

Step 2. Using the chain rule again,

d/dx(cos(3x))=(d(cos(u)))/(du)(du)/(dx)ddx(cos(3x))=d(cos(u))dududx,

where u=3xu=3x and d/(du)(cos(u))-sin(u)ddu(cos(u))sin(u), gives

=(-d/dx(3x)sin(3x) )/(1+cos^2(3x))=ddx(3x)sin(3x)1+cos2(3x)

Step 3. Factor out constants

=-3(sin(3x) )/(1+cos^2(3x))d/dx(x)=3sin(3x)1+cos2(3x)ddx(x)

ANSWER: =-(3sin(3x) )/(1+cos^2(3x))=3sin(3x)1+cos2(3x)